EU Risk Regulators and EU Procedural Law. (September 2014) - Chamon, Merijn
Abstract : Before the Treaty of Lisbon, EU agencies were unknown in the EU's primary law defined procedural law. Today, following (i) the Treaty's entry into force, (ii) the Common Approach on Decentralised Agencies and (iii) the European Court of Justice's ruling in Short–selling it is interesting to take a look at the peculiar position of EU agencies under the EU's primary and secondary law defined procedural law.